A CURIOUS CASE OF CENTRAL RETINAL VEIN OCCLUSION IN A YOUNG PATIENT FOLLOWING DENGUE FEVER - Singh, Anuradha; Sharma, Vikas; Mogra, Shailesh (Indonesian Vitreoretinal Society, 2024)
Introduction: Central retinal vein occlusion (CRVO) is a common ocular disease which can be responsible for significant ocular morbidity in the adult population. It is most commonly associated with lifestyle diseases especially hypertension in older age groups, but may have a variety of etiologies including genetically inherited disorders. Case report: A 27-year-old female patient presented to our out patient department (OPD) with history of diminished vision in left eye of 03 days duration. The patient gave history of contracting dengue fever three weeks prior to the onset of symptoms. On evaluation she was found to have CRVO of the left eye with no macular edema. The patient was investigated for other causes of CRVO and was found to have mildly reduced serum homocysteine and deranged serum iron studies. The patient was managed conservatively with good visual recovery and is presently on follow up for early detection of complications for CRVO. Discussion: The patient presented with multiple etiologies of CRVO, however, each was subclinical in nature. Conservative management for ocular symptoms along with treatment of systemic deficiencies by the physician lead to good visual outcome and generalized well being of the patient. Conclusion: CRVO is being increasingly seen in the younger age group. Multiple etiologies may need to be ruled out, along with lifestyle diseases which are on an incline in the younger population. Close follow up with treatment is required to detect complications early, and provide a good visual outcome. To our knowledge, this is the third reported case of CRVO related to dengue fever.